2017
DOI: 10.1088/1741-4326/aa70b1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen isotope transport across tungsten surfaces exposed to a fusion relevant He ion fluence

Abstract: Tungsten targets are exposed to controlled sequences of D 2 and He, and He and D 2 plasma in the Pisces-A linear plasma device, with a view to studying the outward and inward transport of D across a He implanted surface, using thermal desorption mass spectrometry. Differences in transport are interpreted from changes in peak desorption temperature and amplitude for D 2 release, compared against that of control targets exposed to just D 2 plasma. Desorption data are modeled with Tmap-7 to infer the nature by wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Doerner 2 , C. Xu 4 , J.P. Zhu 4 and E.G. Fu 4,a It is thought that this is caused by the so-called barrier effect in which the implanted He ions form a thin (few tens of nm) He nanobubble layer in the sample and act to reduce the D retention either via the formation of interconnected pathways to the sample surface, leading the D ions to diffuse back to the plasma and resulting in the D retention decreasing, or by the formation of a diffusion barrier to the D atoms, or both [6]. On the other hand, many studies [7][8][9][10][11] have shown that radiation damage in W induced e.g.…”
Section: Nuclear Fusionmentioning
confidence: 99%
“…Doerner 2 , C. Xu 4 , J.P. Zhu 4 and E.G. Fu 4,a It is thought that this is caused by the so-called barrier effect in which the implanted He ions form a thin (few tens of nm) He nanobubble layer in the sample and act to reduce the D retention either via the formation of interconnected pathways to the sample surface, leading the D ions to diffuse back to the plasma and resulting in the D retention decreasing, or by the formation of a diffusion barrier to the D atoms, or both [6]. On the other hand, many studies [7][8][9][10][11] have shown that radiation damage in W induced e.g.…”
Section: Nuclear Fusionmentioning
confidence: 99%
“…11,12 Furthermore, the research on the retention of hydrogen and isotopes on the surface holds significant potential for nuclear fusion energy. 13,14 Tokamak reactors commonly employ hydrogen and isotopes as fuel sources, and the interaction of these species in the plasma state on the inner walls of the reactor has garnered significant attention in current studies. 15−18 Moreover, hydrogen storage assisted by plasma has garnered attention from several research groups.…”
Section: Introductionmentioning
confidence: 99%
“…H 2 and D 2 are commonly applied to passivate Si substrates in the microelectronic industry to prevent contamination, such as H 2 O, which is present in the base pressure of standard vacuum vessels. Additionally, passivation finds various applications in thin film technologies, serving as anticorrosive protection and interface functionalization and creating hard coatings. Passivation of dangling bonds is crucial in hydrogenated amorphous silicon materials. , Furthermore, the research on the retention of hydrogen and isotopes on the surface holds significant potential for nuclear fusion energy. , Tokamak reactors commonly employ hydrogen and isotopes as fuel sources, and the interaction of these species in the plasma state on the inner walls of the reactor has garnered significant attention in current studies. Moreover, hydrogen storage assisted by plasma has garnered attention from several research groups. , To control the physical–chemical mechanisms of passivation, factors like the surface state, temperature, and sticking coefficient must be taken into consideration. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it seems obvious that the retention of hydrogen isotopes should closely follow the evolution of damage with the dose. However, hydrogen isotopes retention is a complicated phenomenon because it is the result of many different parameters such as the material grade (structure and impurity level) [24], the material temperature [25], surface condition [26], and it depends critically on the incoming particle flux, its energy and composition as hydrogen bubble formation occurs above a certain solute concentration [27,28]. Eventually, macroscopic defects, such as blisters, develop [24,[29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%